Uji aktivitas antibakteri formulasi sediaan gel antijerawat ekstrak etanol kulit buah alpukat (Persea americana Mill) terhadap bakteri Staphylococcus aureus - Novi Yuliandari; Yayuk Putri Rahayu; Minda Sari Lubis; Rafita Yuniarti (Journal of Pharmaceutical and Sciences, 2023)
The avocado peel contains flavonoids, saponins, tannins, steroids, and glycosides and has antimicrobial properties. Staphylococcus aureus is a gram-positive bacteria and typical skin microorganism that causes acne. It produces lipase, which breaks down free fatty acids from skin lipids. The gel preparation was chosen. It is better used in treating acne because it does not contain oil or affect acne. This study aimed to determine whether the ethanol extract of avocado peel can be used as an anti-acne gel and to choose the inhibitory power of the gel preparation against Staphylococcus aureus. The ethanol extract of avocado peel was prepared using the percolation method; the extract was formulated into anti-acne gel with 10%, 20%, and 30%. Then, a physical evaluation of the preparation was carried out by assessing organoleptic, homogeneity, pH, viscosity, adhesion, spreadability, irritation, skin moisture, and syneresis. Then, the activity of Staphylococcus aureus bacteria was tested on gel preparations. The result is that the ethanol extract of avocado peel can be formulated into gel preparation. It has a distinctive aroma, is homogeneous, has a pH range of 6,2-6,9, has a value of viscosity, spreadability, and good adhesion, does not irritate, can moisturize the skin, and does not cause syneresis. The gel preparation had antibacterial activity against Staphylococcus aureus, namely a concentration of 10% inhibition of 14.56 mm, 20% inhibition of 19.46 mm, and 30% inhibition of 21.2%, so the interpretation of the inhibition zone was included in the susceptible category.